Aquablation in men with benign prostate hyperplasia: A systematic review and meta-analysis. (31st March 2023) - Chen, David C.; Qu, Liang; Webb, Howard; Qin, Kirby; Chislett, Bodie; Xue, Alan; Khaleel, Sari; De Jesus Escano, Manuel; Chung, Eric; Adam, Ahmed; Bolton, Damien; Perera, Marlon
Abstract: Objective: The aim of the study is to investigate improvements in lower urinary tract symptoms in men with benign prostatic hyperplasia (BPH) treated with prostatic Aquablation. Materials and methods: We performed a literature search of clinical trials using the MEDLINE, Embase, and Cochrane Library databases and retrieved published works on Aquablation for the treatment of BPH up to August 2021. Unpublished works, case reports, conference proceedings, editorial comments, and letters were excluded. Risk of bias was assessed using the ROBINS-I tool. Raw means and mean differences were meta-analyzed to produce summary estimates for pre- versus post-International Prostate Symptom Scores, maximum flow rate, and male sexual health questionnaire value changes. An inverse-variance weighted random effects model was used. Results: Seven studies were included in this review (n = 551 patients) that evaluated various urological parameters. At 3 months, the International Prostate Symptom Scores raw mean difference from baseline was −16.475 (95% confidence interval [CI], −15.264 to −17.686; p < 0.001), with improvements sustained for 12 months. Similarly, maximum flow rate improved by +1.96 (95% CI, 10.015 to 11.878; p < 0.001) from pre to 3 months postoperatively. In addition, the male sexual health questionnaire change pooled effect size was −0.55 (95% CI, −1.621 to 0.531; p = 0.321) from preintervention to postintervention at 3 months. Meta-analyses of some outcomes showed large statistical heterogeneity or evidence of publication bias. Conclusions: Aquablation seems to improve lower urinary tract symptoms in men with BPH while providing relatively preserved sexual function. Further research is required to confirm these preliminary results.